2009
DOI: 10.1080/08941930903214768
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Pre- and Postoperative Range of Motion Utilizing Three Cruciate-Retaining Total Knee Prostheses

Abstract: We prospectively examined the relationship between pre- and postoperative range of motion utilizing three cruciate retaining knees with various mechanical flexion potentials, i.e., two at about 130 degrees -135 degrees (one with posterior lip and the other without) and the third at about 140 degrees -145 degrees . All groups demonstrated mean flexion and range of motion of 116 degrees -122 degrees at one year. Combining data from the three cohorts, patients with the following preoperative flexion values achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In answer to our second question, we found that Asian patients with poorer preoperative ROM gained more flexion than their counterparts with better preoperative ROM, who lost flexion following TKA. Similar findings have been reported by several Western studies. In a landmark study conducted by Parsley et al ., 313 posterior‐cruciate‐retaining TKAs were assessed to determine the influence of preoperative ROM on postoperative ROM.…”
Section: Discussionsupporting
confidence: 91%
“…In answer to our second question, we found that Asian patients with poorer preoperative ROM gained more flexion than their counterparts with better preoperative ROM, who lost flexion following TKA. Similar findings have been reported by several Western studies. In a landmark study conducted by Parsley et al ., 313 posterior‐cruciate‐retaining TKAs were assessed to determine the influence of preoperative ROM on postoperative ROM.…”
Section: Discussionsupporting
confidence: 91%
“…In general, the change in motion following TKA is inversely related to the preoperative value, that is, patients presenting with restricted motion tend to gain much motion after surgery while those with a high degree of motion initially tend to stay about the same, or perhaps lose a small amount of motion, after surgery [ 20 , 23 ]. While this “regression toward the mean” is well documented, a potential gender effect has not been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The Vanguard knee (Biomet, Warsaw, IN) is a high-flex design as it can mechanically accommodate up to 145° of flexion although that achieved clinically may be less due to the soft tissue restraint of the patient [ 20 , 23 ]. From September 2004 to April 2013, a consecutive series of 1,328 patients received 1,785 cruciate-retaining (CR) knees of this type via a medial parapatellar approach using cemented fixation, including 802 women (1,069 knees) and 526 men (716 knees).…”
Section: Methodsmentioning
confidence: 99%
“…The high flex CR knee utilized for addressing the issue was selected, to some degree, because there has been big cohort, mid-term studies published recently on present framework to give a standard to which our outcomes might be analysed [20,28]. [20,23,29].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that there would be no gender difference in those measurements. [20,23]. All the patella was resurfaced.…”
Section: Introductionmentioning
confidence: 99%